Pengembangan Media Flashcard Pada Materi Keanekaragaman Hayati Sebagai Media Pembelajaran Biologi Di SMK N 9 Merangin Kelas X - Lina Nurul Mardianti; Rodiantifitri Nengsih; Pitri Handayani (Pendidikan Biologi STKIP YPM Bangko, 2021)
The bckground of this research is that Flashcard media has not been develop that describes the material on biodiversity. For learning, Biology teachers only use textbook media. The textbook used in Biology learning is still ineffective because Biology is related to nature, and there are only a few pictures. This makes learning less attractive, the language used is difficult to understand, and less effective so that student in learning are bored, sleepy. Saturated because the images presented are colorless of it can be said that student interest in learning is low. To overcome this, the researchers developed Flashcard media on Biodiversity material. This research aims to product valid Flashcard media on Biodiversity material in SMA/SMK and equivalent. This research is a development research using a 4-D model which includes the stages of define, design, develop, and disseminate. The subject of this study consisted of 7 validators, to test the validity of 2 teachers of SMK N 9 Merangin and 5 lectures of STKIP YPM Bangko. The research instrument was a questionnaire for the validity of the Flashcard media, then the data were analyzed using descriptive analysis. Based on the results of this study, a valid Flashcard media was produced. The resulting Flashcard media was declared very valid by the validator with a validity value of 91%. So it can be concluded that the resulting Flashcard media is valid.